Optimization and performance analysis of a portable solar cooker system - Amirul Azfar, Elias (2012)
In rural areas where supply of electricity and energy resource are very scarce,cooking will mostly being done using conventional way by burning woods, A passive solar cooker is one of the solution to overcome the environmental problemcaused the conventional cooking method as well as providing the residents a free andconvenient way to cook. Parabolic dish was fabricated using fibre glass and the system is designed considering the factor of portability and performance. Many typeof material could be use as the reflector thus, need to investigate the better materialto be use to get the high percentage of heat radiation. Besides, experiment had beenrun twice, without thermal energy storage and without thermal energy storage.Experiment has been run using 3 spotlight to consider having radiation of 880W/m².The testing and performance of the concentrated solar thermal cooker (CSTC) hasbeen investigated by measuring a 1kg steel of bar temperature. CSTC without using thermal energy storage able to heat up the steel bar to 100°C within 1 hour compare to CSTC with using thermal energy storage able to heat up the steel bar to 65°C within 1 hour. Efficiency of the solar cooker without thermal energy storage ranging up to 12.12% and solar cooker with thermal energy storage is up to 8.92%.